Simulasi Inverter Tiga Fasa Dengan Teknik Pengontrolan Sinusoidal Pulse Width Modulation Aplikasi Pada Pembangkit Listrik Tenaga Surya - Arzul Arzul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
The need for electrical energy has increased from time to time in accordance with the increase in population and industrial development. However, the current availability of electrical energy comes from fossil energy and this makes the availability of fossil energy in the world dwindling. Therefore, renewable energy is needed to meet future electrical energy needs. In Indonesia, there is a lot of availability of renewable energy such as wind energy, solar energy, water energy and others. This research will focus on solar energy using a photovoltaic inverter with switching control techniques using sinusoidal pulse width modulation (SPWM). The results of SPWM design for inverter switching control have been simulated using Mathlab Simulink. The results of this simulation have resulted in the inverter output waveform approaching a perfect sinusoid. The content of voltage harmonics in the output waveform of this inverter is already below the standard set with a THDv of 2.69%. Meanwhile, the inverter output current harmonic is THDi 15.09%. From the results of this study, it can be seen that the inverter output using the SPWM control technique has been successfully implemented with harmonics below the specified